Precision and Paradigm Shift: Transforming Land and Building Tax Assessment Through Uav-Lidar Derived High-Resolution 3d Spatial Data - Arie Yulfa; Muhammad Giatman; Syarief, Azhari; Ramadhan, Risky; Zikra, Afdhal (Sumatra Journal of Disaster, Geography and Geography Education, 2026)
The conventional Land and Building Tax (PBB) evaluation methods in Indonesia, namely in Baso District, Agam Regency, depend on two-dimensional measures with accuracy rates ranging from 85% to 95%, resulting in possible revenue deficits and assessment inconsistencies. This work seeks to create and execute a more precise tax assessment system utilizing high-resolution 3D spatial data obtained by UAV-LiDAR technology. The study utilizes a quantitative applied methodology, employing a DJI Matrice 350 RTK outfitted with LiDAR sensors for data acquisition. Data processing with DJI Terra and TerraSolid software produces Digital Terrain Models (DTM) and Digital Surface Models (DSM), facilitating accurate land boundary delineation and 3D building digitization. The findings indicate a substantial enhancement in spatial measuring accuracy, attaining 97-99% precision relative to traditional approaches. The implementation facilitates thorough property evaluation via precise measurements of building heights, volumes, and land areas, thereby offering a more dependable foundation for tax computations. The study suggests that, despite constraints including elevated initial costs and training demands, the inclusion of UAV-LiDAR technology significantly improves the accuracy, efficiency, and transparency of PBB assessments, representing a notable improvement in contemporary property tax administration systems.